2017
DOI: 10.6018/analesps.33.2.265831
|View full text |Cite
|
Sign up to set email alerts
|

¿Existe relación entre uso problemático de Internet y las respuestas de ansiedad social, obsesivo-compulsivas y el bienestar psicológico en adolescentes?

Abstract: <span style="font-family: 'Garamond',serif; font-size: 8pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-language: AR-SA; mso-bidi-language: AR-SA;">Eluso<span style="letter-spacing: -0.05pt;">e</span><span style="letter-spacing: 0.1pt;">x</span><span style="letter-spacing: -0.15pt;">c</span><span style="letter-spacing: -0.05pt;">e</span>sivode<span sty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 36 publications
2
5
0
3
Order By: Relevance
“…The nding of the current study show a signi cant association of internet addiction and social anxiety. Our study strongly supported by a study done in Spain, which revealed a signi cant association between internet addiction and social anxiety (57).…”
Section: Discussionsupporting
confidence: 89%
“…The nding of the current study show a signi cant association of internet addiction and social anxiety. Our study strongly supported by a study done in Spain, which revealed a signi cant association between internet addiction and social anxiety (57).…”
Section: Discussionsupporting
confidence: 89%
“…The associations between altered affective domain and IUD have been previously documented (e.g., Li et al, 2019 ), however, the association of IUD with the interaction between affective - and impulsive-compulsive domain has been less understood. Of note, while young people with social anxiety have been suggested to use the Internet as a means for interacting with others (i.e., positive reinforcer), young people with obsessive-compulsive symptoms would use the Internet excessively to modulate compulsive anxiety (negative reinforcer; Bernal-Ruiz et al, 2017 ). Future studies should further explore possible moderating roles of depression and anxiety in IUD as potentially useful variables in the context of clinical assessment and diagnosis formulation.…”
Section: Discussionmentioning
confidence: 99%
“…To identify and conceptualize diagnostic criteria for IUD, several studies assessed specific psychological characteristics of individuals with IUD (e.g., Peterka-Bonetta et al, 2019 ). Among these studies, it has been mainly reported that individuals with IUD are more likely to have symptoms related to the affective and impulsive-compulsive domains , and substance addictions (e.g., Anderson et al, 2017 ; Bernal-Ruiz et al, 2017 ). The interaction between low mood regulation and high stress reactivity ( affective domain ) and high impulsivity/poor inhibitory control ( impulsive-compulsive domain ) has been suggested to be a key aspect of both behavioral addiction and IUD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La ansiedad y su relación con el UPI ha sido estudiada ampliamente (Baloğlu et al, 2018;Bernal-Ruiz et al, 2017;Bozkurt et al, 2013;Cole y Hooley, 2013;Çuhadar, 2012;De Vries et al, 2018;Demirci et al, 2015;Derbyshire et al, 2013;Durak y Şenol-Durak, 2013;Huan et al, 2014;Ioannidis et al, 2018;Kim et al, 2016;Kim y Davis, 2009;Kitazawa et al, 2018;Lee et al, 2018;Lee y Stapinski, 2012;Odaci y Çikrikci, 2017aOdaci y Çikrikci, , 2017bOdaci y Kalkan, 2010;Romano et al, 2017;Tokunaga, 2014;Truzoli et al, 2016). Los estudios recogen diferentes instrumentos para medir la ansiedad, entre ellos: State-trait Anxiety Inventory (STAI) (25%); Liebowitz Social Anxiety Scale (LSAS) (20%); DASS (15%); K-SADS-PL (10%), Interactional Anxiousness Scale (IAS) (10%); Barratt Impulsive Scale (BIS) (5%), Social Phobia and Anxiety Inventory (SPAI) (5%), Beck Anxiety Inventory (BAI) (5%), Sensation-seeking Scale (SS) (5%).…”
Section: Ansiedadunclassified